The Heredia Declaration: Principles on the use of Artificial Intelligence in Scientific Publishing: English translation - Penabad-Camacho, Liana (2024)
Introduction. The Heredia Declaration proposes, from the perspective of scientific publishing, a series of considerations for the responsible use of artificial intelligence (AI) in research processes leading to scientific publication. The use of AI as a tool must be evidenced and transparent for a clear, traceable, and reproducible exercise of knowledge. Attention is drawn to the challenges of incorporating AI into scientific publishing in terms of the diversity of options, the need to prevent the spread of bias and misinformation, and the respect for intellectual property. Principles. Principles are organized into four groups: general, roles of authorship, peer review, and editing. They highlight the importance of using AI as a tool whose results are filtered by humans who, from an ethical and responsible perspective, transparently report which model was used, what was consulted, and when the inquiry took place. Final reflection. The article highlights that this is a constantly evolving scenario whose ultimate goal must be human well-being and quality of life.